THU0516 Health-Related Quality of Life in Patients with Newly Diagnosed JIA with Different Treatment Strategies (Acute-JIA Study). (9th June 2015) - Tarkiainen, M.; Tynjälä, P.; Vähäsalo, P.; Kröger, L.; Aalto, K.; Malin, M.; Putto-Laurila, A.; Honkanen, V.; Lahdenne, P.
Abstract : Background: Health-related quality of life (HrQoL) is impaired in patients with juvenile idiopathic arthritis (JIA). Objectives: To study HrQoL in patients with newly diagnosed JIA on three treatment strategies. Methods: In ACUTE-JIA Study (1), 60 patients were randomized into three treatment arms: infliximab with methotrexate (TNF); a combination of methorexate, hydroxychloroquine, and sulphasalazine (COMBO), or methotrexate monotherapy (MTX). During the first year, at seven study visits, efficacy was measured with ACRped criteriae and HrQoL with Child Health Questionnaire (CHQ). Results: All 20 patients continued intended therapy until week 54 in the TNF, 16 in COMBO, and 11 in MTX group. The last CHQ scores before discontinuation of the therapy were carried forward. Physical summary scores (PhS) and Psychosocial summary scores (PsS) improved from week 0 to 54 (Table 1 ) in all treatment groups with no differences between the groups. In all groups, significant improvements in PhS occurred over time until week 24 of the study, but not after that. In univariate analyses, CHAQ at weeks 0 (β=20.07; p<0.001) and 12 (β=-14.75; p=0.04), and cumulative use of steroids (β=-3.89; p=0.006) correlated with absolute change in PhS from week 0 to 54 (R 2 =0.381). Conclusions: During the first year of treatment of JIA, HrQoL improved in all treatment categories. Patients and parents seem to acknowledge a significant change in PhS during the first half-year, but not thereafter. References: Tynjälä P, Vähäsalo P, Tarkiainen M, et al. Aggressive Combination Drug Therapy in Very Early Polyarticular Juvenile Idiopathic Arthritis (ACUTE-JIA): a multicentre randomised open-label clinical trial. Ann Rheum Dis. 2011 Sep;70(9):1605-12. Disclosure of Interest: None declared